Perancangan Dan Pembuatan Sistem Informasi Penjualan Apotek Berbasis Desktop (Studi Kasus Pada Apotek “Tiara”) - Sena, I Gede Wiarta; Trianto, Edwin Meinardi; Octadianto Soedargo, David Saputra; R. C. D., Michael Komang (LPPM STIKI MALANG, 2024)
The important thing that must be done by a company is to ensure that the transaction process can run quickly and accurately. Therefore, companies must update their systems so that business processes can run optimally. Apotek Tiara still uses a manual transaction system, so there are many errors and problems that can harm the company. Therefore it is necessary to create a desktop-based application that can be used for the sales transaction process along with the order throwing transaction process. The purpose of this study is to develop and create a desktop-based sales information system that can be used by Tiara Pharmacy to improve operational efficiency and automate the sales process, stock recording, and financial reports. The method used in developing information systems is the agile method. The resulting system consists of a login process based on user access rights, a cashier process, updating item or drug data, a report generation process, and a delivery process. The result of this research is a sales information system at the Tiara pharmacy in the city of Surabaya which is specially made so that it can carry out an accurate data collection process.